Porous MgO-stabilized CaO-based powders/pellets via a citric acid-based carbon template for thermochemical energy storage in concentrated solar power plants - Wang, Ke; Gu, Feng; Clough, Peter T.; Zhao, Pengfei; Anthony, Ben (Elsevier, 2020)
The reversible CaO/CaCO3 carbonation reaction (CaL) is one of the most promising candidates for high-temperature thermochemical energy storage (TCES) in concentrated solar power plants (CSP). Here, a sacrificial citric acid-based carbon template was developed to produce high-performance CaO-based sorbents to mitigate the progressive deactivation with sequential carbonation-calcination cycling. The carbon template was formed through in situ pyrolysis of citric acid in a simple heating process under nitrogen. After a secondary calcination step in air, a stable porous MgO-stabilized nano-CaO powder was generated and achieved high long-term effective conversion due to its resistance to pore plugging and sintering. By dry mixing citric acid with limestone-dolomite mixtures, this procedure can also be applied to synthesize MgO-stabilized CaO pellets via an extrusion–spheronization route, which resulted in comparably stable and effective conversion as the optimized CaO powder. Additionally, the considerable mechanical strength of MgO-stabilized CaO pellets should enable their realistic application in fluidized bed reactors. Thus, this simple, cost-effective and easily-scalable synthesis technique appears to have great potential for CSP-TCES under high temperature operation.
Keywords: thermochemical energy storage; concentrated solar power; CO2 capture